A novel and sensitive sarcosine biosensor based on organic electrochemical transistor. (1st June 2019) - Hu, Jin; Wei, Weiwei; Ke, Shanming; Zeng, Xierong; Lin, Peng
Abstract: Organic electrochemical transistors (OECTs) are successfully used for sensitive and selective detection of sarcosine, which is recognized as a potential non-invasive specific biomarker for prostate cancer. The sensitivity and selectivity of OECT-based sarcosine sensors are significantly improved by modifying sarcosine oxidase (SOx) on platinum-plated anodized aluminum oxide (AAO) gate electrodes. The device with Nafion-SOx/Pt/AAO gate electrode shows the excellent sensing performance and the sarcosine can be detected in a linear range from 50 nM to 100 μM with a detection limit of 50 nM, which is satisfied with the clinical range of prostate cancer levels in human urine (20 nM–5 μM) and much lower than that of conventional electrochemical methods. Meanwhile, the selectivity of the sensor is also well proved. This work indicates a novel OECT-based sarcosine biosensor with high sensitivity and selectivity for the first time, which has the prospect of a wide range of routine testing. Graphical abstract: Image 1